Standardized Infection Ratio for Surgical Site Infection after Colon Surgery: Discord in Models Measuring Healthcare Quality. (30th August 2016) - Chinn, Raymond; Lempp, Jason M.; Huang, Susan S.; Murthy, Rekha; Torriani, Francesca J.; Daley, Jacqueline; Dekker, Elaine; Goss-Bottorff, Barbara; Kaler, Wendy; Meyer, Karen; Myers, Frank; Nichols, Amy; et al.
Abstract : The government publishes 3 different public report surgical site infection (SSI) metrics, all called standardized infection ratios (SIRs), that impact perceived hospital quality. We conducted a non-random cross-sectional observational pilot study of 20 California hospitals that voluntarily submitted colon surgery and SSI data. Discordant SIR values, leading to contradictory conclusions, occurred in 35% of these hospitals. Infect Control Hosp Epidemiol 2016;1–5